Analisis dan Perancangan Sistem Informasi Akuntansi Kas pada Satker PSP.TP Dinas Pertanian Tanaman Pangan Provinsi Jambi - Siti Rahayu; Joni Devitra (LPPM Universitas Dinamika Bangsa, 2017)
Currently a mangement of cash accounting system on satker PSP.TP department of Agriculture Jambi province is stillnot optimal, application management is still in the form of separate and has the deficiency that in made a report on therealization of each of the Parties in detail. Because at the time of inputting his account receipts search view there is nodetailed descriptions of activities, then in making a detailed report on the realization of its still using Ms. Excel, so thesystem can not produce a detailed report on the realization automatically. So that raises some problems, includingerrors in inputting activity account code, the slow process of data search because it involves a lot of applications. Toovercome these problems, in this research designed information system of cash accounting that is expected to assistthe side satker PSP.TP in accelerating data management. This research resulted in the design information systems ofcash accounting related to some reports that the general book, realization of the budget , the details realization of thebudget, bank books, and taxes. The method used is the object-oriented approach using UML (unified modelinglanguage) that is use case diagrams, class diagrams and activity diagrams. This research produced a prototype thatcan be implemented further so that resulting in a information system of cash accounting that can be implemented insatker PSP.TP Department of Agriculture Jambi Province.